THE ROLE OF ARTIFICIAL INTELLIGENCE IN MONITORING PEDESTRIAN MOVEMENT - Javohir Karimov (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
In busy cities, people moving around is like a lively dance that keeps the city alive. Watching how people move is super important because it helps make smart decisions about how the city is set up, how to keep everyone safe, and how traffic works. Cities are like living things with people going through streets, squares, and crossings. Keeping an eye on how people move is like checking the pulse of the city. It helps city planners and leaders understand how people move around the city. Each step people take tells a story, and watching them helps us understand the unique language of city life. Urban planning is like a careful dance between making things work well and making them look nice. Watching how people move helps planners understand what people like without having to ask them directly. Knowing where lots of people go, where they gather, and how they act helps create places that look good and work well for everyone. This article talks about how watching how people move is super important. It explains how this monitoring is like the key to making cities not just busy but also safe, eco-friendly, and well-connected.